The Phenomenon of the Month of Sela in the Indonesian Capital Market - Arini Putri Helanda; Ani Wilujeng Suryani (AKRUAL: JURNAL AKUNTANSI, 2020)
Seasonal anomalies cause market inefficiency by affecting the mean and volatility of stock returns, and allow investors to obtain abnormal returns. In Indonesia, there is the month of Sela which is believed as an unlucky month so that many people avoid this month to hold ceremonial activities. As a result, the economy declines in the month of Sela and possibly, the return will also drop in this month. Therefore, this research aims to reveal whether the month of Sela is a seasonal anomaly. This research tested two hypotheses; the effect of the mean and volatility of price index return by using the GARCH model. To examine the effect of the month of Sela on the mean and volatility of return of price index, we collected the data on Indonesian Composite Index and 10 sectoral indices from 2009 to 2019 on three Javanese months, Sawal, Selo and Besar. In total, we collected 7.095 returns data. The month of Sela was a seasonal anomaly that the average and volatility of returns during the month of Sela were lower than those during the months of Sawal and Besar. These results also indicated that during the months of Sawal and Besar, the price index was more volatile than it was during the month of Sela. This research is useful for investors in considering their investment decisions to obtain an abnormal return. This research also contributes to the literature by adding new knowledge about seasonal anomalies that exist in Indonesia.